Alkaloid compound from Tombili (Caesalpinia bonduc) as biopesticide agent on rice plants - Weny J.A Musa; Suleman Duengo; Ahmad Kadir Kilo; Boima Situmeang (Jurnal Pendidikan Kimia (JPKim), 2020)
The purpose of these study is to determine the effect of active compound from tombili seed extract as a vegetable pesticide in the prevention of soil pest in rice plants. The method of these researches is isolation to obtain pure isolates, characterization by using infrared spectrophotometer (IR) and UV-VIS spectrophotometer then following biological test. The isolates obtained were tested positive for phytochemical containing alkaloid compounds and characterized as amorphous crystals. Identification of IR spectrophotometer generate a functioning -NH wave group of the wavelengths region of 3423.4 cm-1, bend C-N at wave number 1242.1 cm-1, C-H stretch at wave number 2925.8 and 2854.5 cm-1, bend C-H at 1475 wave numbers 1540 cm-1, carbonyl group (C = O) at the 1720.4 cm-1 wave number which is probably an alkaloid compound. The UV-VIS spectrophotometer results in a maximum absorption at 209.9 nm wavelengths indicated the presence of double bonds between the C = O functional group suspected as a result of the successive electronic transitions to n-π * and n-σ *. The result of biological test showed that methanol extracts of tombili seed can be used as a vegetable pesticide in pest prevention on rice plants, the most effective concentration used in this biological test is at 0.1% concentration, with very high effectiveness in eradicating pest on rice plants.Keywords: Tombili, Alkaloid, Biopesticide